Alterations in prefrontal cortical neuregulin-1 levels in post-pubertal rats with neonatal ventral hippocampal lesions - Watanabe, Kenya; Nakagawasai, Osamu; Kanno, Syu-ichi; Mitazaki, Satoru; Onogi, Hiroshi; Takahashi, Kohei; Watanabe, Kei-ichiro; Tan-No, Koichi; Ishikawa, Masaaki; Srivastava, Lalit K.; Quirion, Remi; Tadano, Takeshi (Frontiers in Behavioral Neuroscience, 2022)
Genetic studies in humans have implicated the gene encoding neuregulin-1 (NRG-1) as a candidate susceptibility gene for schizophrenia. Furthermore, it has been suggested that NRG-1 is involved in regulating the expression and function of the N-methyl-D-aspartate receptor and the GABAA receptor in several brain areas, including the prefrontal cortex (PFC), the hippocampus, and the cerebellum. Neonatal ventral hippocampal lesioned (NVHL) rats have been considered as a putative model for schizophrenia with characteristic post-pubertal alteration in response to stress and neuroleptics. In this study, we examined NRG-1, erb-b2 receptor tyrosine kinase 4 (erbB4), and phospho-erbB4 (p-erbB4) levels in the PFC and the distribution of NRG-1 in the NVHL rats by using immunoblotting and immunohistochemical analyses. Neonatal lesions were induced by bilateral injection of ibotenic acid in the ventral hippocampus of postnatal day 7 Sprague-Dawley (SD)-rats. NVHL rats showed significantly decreased levels of NRG-1 and p-erbB4 in the PFC compared to sham controls at post-pubertal period, while the level of erbB4 did not differ between sham and NVHL rats. Moreover, microinjection of NRG-1 into the mPFC improved NVHL-induced prepulse inhibition deficits. Our study suggests PFC NRG-1 alteration as a potential mechanism in schizophrenia-like behaviors in the NVHL model.